The Impact of Exchange Rate and Money Supply Changes on Gross Domestic Product: An Applied Study on the Libyan Economy for the Period (1995-2020) (Comprehensive Journal of Science, 2026)
This study aims to demonstrate the effect of changing the exchange rate and money supply on the gross domestic product for the period (1995-2020) and to build a standard model that explains the impact of the economic variables represented in the exchange rate of the Libyan dinar and the money supply. The study was based on the hypothesis that the independent variables under study have direct effects on Gross domestic product as a dependent variable. In this study, the descriptive approach was relied upon to determine the theoretical framework and the quantitative analytical approach for analyzing quantitative data through the E-Views program using the (ARDL) methodology, as it became clear from the results of the estimate and the BOUNDS Test, which indicates the existence of A co-integration relationship between the variables of the study, and the value and sign of the negative and significant error correction coefficient (0.0002) also demonstrated that the short-term errors are corrected by an estimated rate of 130% in the long-term to return to the equilibrium position, and the structural stability test of the model confirmed that the cumulative sum of the residuals (cusum) And the cumulative sum of the squares of the residuals (cusum of Squares) is located within the critical limits, which indicates that there is stability and harmony between the results of the short and long term. The relationship between the study variables corresponds to the reality of the Libyan economy during the study period (1995-2020 AD).